PENGARUH KUALITAS AUDIT DAN KUALITAS PELAPORAN KEUANGAN TERHADAP EFISIENSI INVESTASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2017 – 2019 - Firawan, Panji Aldy; Dewayanto, Totok (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of audit quality and financial reporting quality on investment eﬃciency where the variables used in this study are the dependent variable (investment eﬃciency) and the independent variable (audit quality and financial reporting quality). The population in this study are sector manufacture listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample was taken by using purposive sampling method. Based on the purposive sampling method, the samples obtained were 113 sampel data for three consecutive years (2017-2019). The analytical method used in this research is multiple linear regression analysis.The results in this study indicate that audit quality and financial report quality have a positive effect on efficiency investment.